PEMANFAATAN SANTAN INSTAN KADALUARSA UNTUK PRODUKSI MINYAK SECARA FERMENTASI - Megmerio Soro; Syaiful Bahri; Erwin Abdul Rahim (KOVALEN: Jurnal Riset Kimia, 2016)
This research use the expired instant coconut milk for 2 months. The goal is to find out whether the coconut milk can be used to produce oil. The method does is with variation of the total  number of laru 0,5 mL oil; 0,75 mL; 1 mL; 1,25 mL; and 1,50 mL by volume per volume (v/v). the fermentation time and 18 hours, 24 hours, 30 hours, and 36 minutes. Results of the study that the amount of oil the oil laru yield the highest oil is 1,50 mL with 28% yield and fermentation time of 30 hours, while the lowest was at the time of fermentation 18 hours i.e. 15%.Keywords: instant coconut milk, expired, coconut oil, yeast, oil, quality and  yield